Analiza towarowa polskiego eksportu rolniczego w latach 1956—1966 - Tetzlaw, Jerzy (Wydział Prawa i Administracji UAM, 1968)
This article examines the dynamic changes in Polish export by means of absolute changes and structural shares which embrace commodity groups. A discussion of the latter necessitates connecting them with the shaping of export of more important agricultural commodities. This is done by the degree of representativeness which is simultaneously the degree of concentration. The latter characterizes the elasticity in adjusting exported bulk commodities to market conditions., In characterizing this elasticity the dependence between the shaping of structural shares in commodity export and their unitary value in export, may be of use as an orientation indicator.
Commodity Analysis of Polish Agricultural Export in the Years 1956—1966